Implementation of Raspberry Pi As A2dp Module On The Quality of Song Reception of Humanoid Robot - Wildan Iswahyudi; Mochamad Farhan Ali Irfani; Muzayana Muzayana; Siti Sendari; Nuzul Zaeni Eki Ramadhanu (Publikasiku, 2024)
This research discusses comparing the performance of Bluetooth communication on Raspberry Pi in controlling dance humanoid robots using external modules and direct communication. This research aims to understand the difference in performance between the two methods, by analyzing data transmission speed, signal stability, and communication latency that affect the quality of robot movement. In addition, this research also aims to evaluate the effectiveness of using simple filters such as low-pass filter circuits to improve the stability of Bluetooth communication on Raspberry Pi. It is hoped that this research can lead to a better understanding of the influence of both communication methods on the quality of dance humanoid robot movements.